Огляд протоколів безпечної маршрутизації в безпроводових мережах стандарту IEEE 802.11 - Євдокименко, М. О.; Шаповал, М. М.; Порохняк, В. Ю. (ХНУРЕ, 2021)
The paper provides an overview of existing secure routing protocols in wireless networks IEEE 802.11. Their benefits and disadvantages are presented. Based on the analysis, requirements were obtained for the development of promising routing solutions at the network level, which, with a high level of protection, will taking into account the features of structural and functional construction of wireless networks; the security parameters of both individual wireless elements and the network as a whole; the limited resources of wireless networks; the information security risks based on existing and identified vulnerabilities on the structural elements of the wireless network; and have acceptable computational complexity and scalability.
Keywords: безпечна маршрутизація; Бездротові мережі стандарту IEEE